2020
DOI: 10.15376/biores.15.2.3125-3135
|View full text |Cite
|
Sign up to set email alerts
|

The influence of culture medium components on the physical and mechanical properties of cellulose synthesized by kombucha microorganisms

Abstract: Preliminary studies are presented showing to what extent nutrients available in the growth environment of Kombucha microorganisms affect the physical and mechanical properties of synthesized cellulose. With an increase in the amount of sucrose in the growth medium and with the presence of additional nutrients, peptone and tea extract, the thickness and strength of the biopolymer increased, while elongation was reduced. The best physical and mechanical parameters were obtained for bacterial cellulose from cultu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 23 publications
(12 citation statements)
references
References 32 publications
0
12
0
Order By: Relevance
“…This could result from the difference in the inoculation method, with only addition of cells in the case of pure cultures as opposed to the addition of 12% (v/v) of kombucha from a previous batch in the other case. The resources of nitrogen, quantitatively and qualitatively, were probably different, and the absence of ethanol could play a role in the rate of cellulose production ( Nguyen et al, 2008 ; Mamlouk and Gullo, 2013 ; Betlej et al, 2020 ). Another hypothesis would lie in the presence of microbial interactions that come with the use of a consortium.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…This could result from the difference in the inoculation method, with only addition of cells in the case of pure cultures as opposed to the addition of 12% (v/v) of kombucha from a previous batch in the other case. The resources of nitrogen, quantitatively and qualitatively, were probably different, and the absence of ethanol could play a role in the rate of cellulose production ( Nguyen et al, 2008 ; Mamlouk and Gullo, 2013 ; Betlej et al, 2020 ). Another hypothesis would lie in the presence of microbial interactions that come with the use of a consortium.…”
Section: Resultsmentioning
confidence: 99%
“…Several of those putative functions of cellulosic biofilms are suspected to be applicable to kombucha pellicle and to play an important role in microbial interaction ( May et al, 2019 ). Very little investigation has been carried out about the kombucha pellicle, especially through the lens of spatial organization and microbial interactions ( Mayser et al, 1995 ; Goh et al, 2012 ; Zhu et al, 2014 ; Coton et al, 2017 ; Sharma and Bhardwaj, 2019 ; Betlej et al, 2020 ). The study of Coton et al (2017) reported differences in microbial composition in the proportion of genera between the liquid phase and the biofilms for yeasts and bacteria using a non-culture dependent method, thus highlighting the impact of two different environments in terms of planktonic and sessile state or oxygen and nutrient access on microbial dynamics ( Coton et al, 2017 ).…”
Section: Introductionmentioning
confidence: 99%
“…Due to the fact that bacterial cellulose of different thickness was obtained on different culture media used in the study, an attempt was made to explain the actual factor that determines the gloss of cellulose. Since in previous studies it was found that with a high sucrose content in the substrate and the addition of nutrient-rich ingredients, significantly thicker polymer layers are obtained (Betlej et al 2020), attempts were made to assess whether the actual factor affecting the gloss of cellulose is its thickness or the composition of the substrate on which the polymer is synthesized. The evaluation of the correlation between the polymer thickness and its gloss made it possible to state that there was a very high relationship between the indicated features (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…The content and specific proportions of nutrients in the culture medium determine the efficiency of the cellulose synthesis process. Simple and readily available nutrients, such as tea extract or peptone, with the optimal amount of the carbon source, allow for good polymer synthesis efficiency; this is additionally characterized by a greater thickness of the film (Betlej et al 2020) and better mechanical parameters (Yim et al 2017). Undoubtedly, taking into account the intended use of bacterial cellulose, it is worth analyzing how the properties and characteristics of the polymer produced under certain conditions interact with each other.…”
Section: Introductionmentioning
confidence: 99%
“…First, the zooglea mats has attracted interest from sustainable fashion and textile industry, because the mats’ properties are similar to properties of clothing materials [19, 20, 21, 22, 23, 24]. Some future applications of the mats might require some loci of a mat to remain alive for sensing purposes, where chemical, tactile or optical stimuli will be mapped onto patterns of electrical activity.…”
Section: Introductionmentioning
confidence: 99%